Clinical supervision of radiography students in Africa: a scoping review of supervisory knowledge, attitudes, and practices - Jacob Leonard Ago; Bismark Ofori-Manteaw; Minh Chau; Wuni Abdul-Razak; Nathaniel Awentiirin Angaag (BMC Medical Education, 2026)
Abstract Introduction Clinical placements are central to radiography education, facilitating the development of professional competence and clinical reasoning. However, theory–practice gaps frequently undermine learning, and across many African contexts, the absence of structured clinical education frameworks may compromise placement quality. This scoping review synthesises reported clinical supervision practices within African radiography contexts to inform evidence-based strategies for strengthening clinical education and improving student outcomes. Methods This review was conducted in accordance with Arksey and O’Malley’s scoping review framework. A systematic search of Scopus, Web of Science, and PubMed was undertaken, supplemented by manual reference screening. Primary empirical studies published in English were included. Data were extracted and synthesised using thematic analysis. Results Of 1,115 records identified, 15 studies from five African countries met the selection criteria. Three themes emerged from the analysis. (I) Limited formal supervisory training, with many radiographers relying on experiential learning and informal “trial-and-error” approaches. (II) While intrinsic motivation to teach was evident, systemic constraints such as high workload, staff shortages, and resource limitations negatively influenced supervisory engagement and contributed to reduced student engagement. (III) Supervisory practices were frequently unstructured, characterised by the absence of standardised guidelines, inconsistent student orientation, and limited formative feedback. These challenges were compounded by student overcrowding and weak institutional collaboration between universities and clinical sites. Conclusion Clinical supervision of radiography students in Africa is constrained by structural, organisational, and pedagogical barriers. Improving student outcomes requires professionalising supervisor roles through formal appointments and incentives, implementing standardised training and continuous professional development programs, and fostering robust partnerships between educational institutions, clinical sites, and professional bodies. Alignment with international best-practice benchmarks is critical to developing a competent, safe, and sustainable radiography workforce across the region.